FRI0452 TOFACITINIB IN PATIENTS WITH PSORIATIC ARTHRITIS: ANALYSIS OF DERMATOLOGIC ENDPOINTS FROM 2 PHASE 3 STUDIES. (June 2019) - Merola, Joseph F.; Papp, Kim; Nash, Peter; Gratacos-Masmitja, Jordi; Boehncke, Wolf-Henning; Thaçi, Diamant; Graham, Daniela; Hsu, Ming-Ann; Wang, Cunshan; Wu, Joseph; Young, Pamela
Abstract : Background: Psoriatic arthritis (PsA) is a chronic, systemic inflammatory disease; the onset of dermatologic symptoms often precedes rheumatic manifestations. 1 Tofacitinib is an oral Janus kinase inhibitor for the treatment of PsA. It has been shown that tofacitinib can improve dermatologic symptoms in patients (pts) with PsA. 2, 3 Objectives: To investigate the efficacy of tofacitinib in improving additional dermatologic endpoints in adult pts with active PsA. Methods: This analysis included data from 2 placebo (PBO)-controlled, double–blind, Phase 3 studies in pts with active PsA and an inadequate response (IR) to ≥1 conventional synthetic disease-modifying antirheumatic drug (csDMARD) who were tumour necrosis factor inhibitor (TNFi)-naïve (OPAL Broaden [12 months; NCT01877668 ]; N=422) 2 or had an IR to ≥1 TNFi (OPAL Beyond [6 months; NCT01882439 ]; N=394). 3 Pts must have had active plaque psoriasis at screening only and were required to receive a stable dose of 1 csDMARD. Pts were randomised to tofacitinib 5 mg twice daily (BID), 10 mg BID, adalimumab 40 mg subcutaneous injection once every 2 weeks (OPAL Broaden only) or PBO (advanced to tofacitinib 5 or 10 mg BID at Month [M]3). Percentage (%) change from baseline (BL) (Δ) in Psoriasis Area and Severity Index (PASI) total score, % of pts achieving ≥75% PASI improvement from BL (PASI75) stratified by BL PASI severity (>0 to ≤10, or >10), and ΔPatient's Global Joint and Skin Assessment-Visual Analogue Scale Psoriasis question (PGJS–VAS Psoriasis) were measured at M1, 3, 6, and at M9 and 12 (OPAL Broaden only).% ΔPASI total score and PASI75 were measured only in pts with BL affected body surface area (BSA) ≥3% and PASI >0. Safety endpoints were also analysed. Results: BL demographics were similar between treatment groups and studies. BL median PASI scores (pts with BL BSA ≥3% and PASI >0) ranged from 5.6 to 7.8 (OPAL Broaden) and 7.1 to 8.8 (OPAL Beyond). BL mean PGJS–VAS Psoriasis ranged from 51.0 to 54.8 (OPAL Broaden) and 53.5 to 58.9 (OPAL Beyond). At M1 and 3, % ΔPASI total score, PASI75 response rates in pts with mild or moderate/severe dermatologic symptoms at BL, and ΔPGJS–VAS Psoriasis were improved vs PBO in tofacitinib-treated pts; these improvements were maintained to M12 in OPAL Broaden and M6 in OPAL Beyond (Table). Similar effects were observed in adalimumab-treated pts vs PBO in OPAL Broaden across these endpoints. Serious adverse events (AEs) and discontinuations due to AEs were similar across treatment groups up to M6 in OPAL Beyond and M12 in OPAL Broaden. Conclusion: In pts with PsA (TNFi-naïve or TNFi-IR), tofacitinib improved dermatologic endpoints, and responses were maintained to the end of each study. Tofacitinib may provide a treatment option for pts with active PsA, including the dermatologic symptoms of PsA. References: [1] Gladman DD, et al. Ann Rheum Dis2005;64:ii14-7. [2] Mease P, et al. N Engl J Med2017;377:1537-50. [3] Gladman D, et al. N Engl J Med2017;377:1525-36. Acknowledgement: This study was sponsored by Pfizer Inc. Medical writing support was provided by Mark Bennett, PhD, of CMC Connect, a division of McCann Health Medical Communications Ltd, Manchester, UK, and was funded by Pfizer Inc. Disclosure of Interests: Joseph F. Merola Consultant for: Biogen IDEC, Abbvie, Amgen, Eli Lilly and Company, Novartis, Pfizer, Janssen, UCB, Samumed, Celgene, Sanofi Regeneron, Merck, and GSK, Kim Papp Grant/research support from: AbbVie, Akros, Allergan, Amgen, Anacor, Arcutis, Astellas, Baxalta, Boehringer Ingelheim, Bristol-Myers Squibb, Can-Fite, Celgene, Coherus, Dermira, Dow Pharma, Eli Lilly, Galderma, Genentech, Gilead, GlaxoSmithKline, InflaRx GmbH, Janssen, Kyowa Hakko Kirin, Leo, MedImmune, Merck (MSD), Merck Serono, Moberg Pharma, Novartis, Pfizer, PRCL Research, Regeneron, Roche, Sanofi-Aventis/Genzyme, Takeda, UCB, Valeant/Bausch Health, Consultant for: AbbVie, Akros, Amgen, Arcutis, Astellas, AstraZeneca, Baxalta, Baxter, Boehringer Ingelheim, Bristol-Myers Squibb, Can-Fite, Celgene, Coherus, Dermira, Dow Pharma, Eli Lilly, Forward Pharma, Galderma, Genentech, Janssen, Kyowa Hakko Kirin, Leo, Meiji Seika Pharma, Merck (MSD), Merck Serono, Mitsubishi Pharma, Novartis, Pfizer, PRCL Research, Regeneron, Roche, Sanofi-Aventis/Genzyme, Takeda, UCB, Valeant/Bausch Health; honoraria: AbbVie, Akros, Amgen, Baxter, Boehringer Ingelheim, Celgene, Coherus, Eli Lilly, Forward Pharma, Galderma, Janssen, Kyowa Hakko Kirin, Merck (MSD), Merck Serono, Mitsubishi Pharma, Novartis, Pfizer, PRCL Research, Sanofi-Aventis/Genzyme, Takeda, UCB, Valeant/Bausch Health; steering committee: AbbVie, Amgen, Boehringer Ingelheim, Celgene, Eli Lilly, Janssen, Kyowa Hakko Kirin, Merck (MSD), Merck Serono, Novartis, Pfizer, Regeneron, Sanofi-Aventis/Genzyme, Valeant/Bausch Health; advisory boards: AbbVie, Amgen, Astellas, Baxter, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Dow Pharma, Eli Lilly, Galderma, Janssen, Merck (MSD) Novartis, Pfizer, Regeneron, Sanofi-Aventis/Genzyme, UCB, Valeant/Bausch Health, Speakers bureau: AbbVie, Amgen, Astellas, Celgene, Eli Lilly, Galderma, Janssen, Kyowa Hakko Kirin, Leo, Merck (MSD), Novartis, Pfizer, Sanofi-Aventis/Genzyme, Valeant/Bausch Health; scientific officer: Akros, Anacor, Kyowa Hakko Kirin, Peter Nash Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Jordi Gratacos-Masmitja Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, Wolf-Henning Boehncke Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, Diamant Thaçi Grant/research support from: AbbVie, Almirall, Amgen, Bio Skin, Biogen-Idec, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Chugai, Dermira, Dignity, Eli Lilly, Forward Pharma, GlaxoSmithKline, Janssen Cilag, Leo Pharma, Novartis, Pfizer, Regeneron, Roche, Sandoz-Hexal, Sanofi, and UCB, Consultant for: AbbVie, Almirall, Bristol-Myers Squibb, Celgene, Dignity, Galapagos, Leo Pharma, Lilly, Novartis, Pfizer, and UCB; honoraria: AbbVie, Almirall, Amgen, Bio Skin, Celgene, Dignity, Janssen, Leo Pharma, Merck Sharp & Dohme, Novartis, Pfizer, Roche-Posay, Sandoz-Hexal, Sanofi, and USB; advisory board: AbbVie, Bio Skin, Bristol-Myers Squibb, Celgene, Dignity, Eli Lilly, Galapagos, GlaxoSmithKline, Janssen Cilag, Leo Pharma, Morphosis, Novartis, Pfizer, Sandoz, Sanofi, and UCB, Daniela Graham Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Ming-Ann Hsu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Cunshan Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Joseph Wu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Pamela Young Shareholder of: Pfizer Inc, Employee of: Pfizer Inc